An Investigation of Test Cases Generation from Activity Diagram - Gupta, Jeena (My University, 2014)
Generation of test cases is the most important issue in the software testing. Thus test cases need to be carefully designed. Test cases can be generated manually or automatically. Activity diagrams are even more challenging for creating test cases. An acti vity diagram consists of flowchart of various activities with transition among them . It s ta tes the internal behaviour of operation s of the system. An activity diagram is used for modelling the dynamic aspects of the system. It h elps in visualizing the sequ ence of activities involved in a control flow. The proposed approach is to automate the generation of test scenarios from activity diagram using DFS method . By using this method, the useless test paths are eliminated which in turn reduces the time complexi ty. This approach also helps in synchronization between various activities. It generates a directed graph called Activity Flow Graph (AF G) and an intermediate table called Activity Dependency Table (ADT) automati cally for each activity diagram . The ADT considers all the dependencies in the form of parent child nodes. Automated test paths are generated from AFG. The test cases are generated to cover all the test paths created by AFG. This approach was found to be effective in reducing the time co mplexity.
Master of Engineering -Software Engineering
Keywords: Activity diagram; acitvity flow graph; test case generation; test cases; test paths